Children's reasoning about peer and school segregation in a diverse society. (16th May 2017) - Tenenbaum, Harriet R.; Leman, Patrick; Aznar, Ana
Abstract: This study examined children's reasoning about gender‐ and religion‐based exclusion in the context of single‐gender and single‐faith schools and play contexts. Young people (twenty‐three 8‐ to 10‐year‐olds and fifty‐three 12‐ to 14‐year‐olds) were asked to judge and reason about the acceptability of exclusion based on gender and religion by children and school principals. Participants rated exclusion based on gender as more acceptable than exclusion based on religion. Exclusion from school contexts was rated as more acceptable than exclusion from play contexts. Participants tended to invoke moral reasons to condemn exclusion when reasoning about religion, whereas they tended to invoke social conventional reasons when reasoning about gender. Young people's greater support for religiously inclusive schooling compared to gender inclusive schooling suggests that societal and governmental acceptance of religious diversity has support from future generations.